Investigation of infrared thermography for crack detection - Iskandar Abdul Halim (2018)
When a component has been used for a very long time, it will undergo fatigue and this might cause cracks to form within it. Therefore, detection of these small cracks caused by fatigue is crucial in predicting the remaining life of the component. It is also crucial in determining whether the component needs to undergo condition-based maintenance or be replaced indefinitely. To detect these small cracks, Non-Destructive Testing (NDT) is usually used as sometimes the cracks are too hard to spot with the naked eyes. One type of non-contact NDT method that may be used for crack detection is Infrared Thermography (IRT). IRT have many benefits and one of them is being a non-contact method. Due to the potential it has shown, one day it might end up replacing the current conventional methods. This project requires the use of IRT to investigate crack detection on various metallic plate specimens. The goal of the stated project is not only to investigate the potential of Thermography using different excitation sources but also to determine the crack detection limit of each source.